2019
DOI: 10.1515/cog-2017-0136
|View full text |Cite
|
Sign up to set email alerts
|

Concept characteristics and variation in lexical diversity in two Dutch dialect areas

Abstract: Lexical diversity, the amount of lexical variation shown by a particular concept, varies between concepts. For the concept drunk, for instance, nearly 3000 English expressions exist, including blitzed, intoxicated, and hammered. For the concept sober, however, a significantly smaller number of lexical items is available, like sober or abstinent. While earlier variation studies have revealed that meaning-related concept characteristics correlate with the amount of lexical variation, these studies were limited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, a shortcoming of this study is that we did not take into account characteristics of the concepts themselves. Previous research has shown that properties like the sensitivity to affect of a particular meaning may influence the amount of variation that is found (Franco et al, 2019; also see Weinreich, 1968:58-59). Additionally, it may be necessary to take into account the period when a particular concept or artifact was introduced into the Dutch culture and language.…”
Section: Discussionmentioning
confidence: 97%
“…However, a shortcoming of this study is that we did not take into account characteristics of the concepts themselves. Previous research has shown that properties like the sensitivity to affect of a particular meaning may influence the amount of variation that is found (Franco et al, 2019; also see Weinreich, 1968:58-59). Additionally, it may be necessary to take into account the period when a particular concept or artifact was introduced into the Dutch culture and language.…”
Section: Discussionmentioning
confidence: 97%
“…However, the dictionary also contains entries for several jocular terms for body parts (e.g., for the head or mouth), children's names for body parts, taboo meanings (e.g., names for male and female genitalia), as well as concepts that are cognitively less salient, referring to parts of the body that might not turn up often in everyday conversations (e.g., dimples, or the upper part of the back). For the basic vocabulary concepts, we expect to find little lexical variation, whereas more variation can be expected across the dialect area for the jocular terms, children's names, and taboo and non-salient concepts (see Speelman and Geeraerts, 2008;Geeraerts and Speelman, 2010;Franco et al, 2019b).…”
Section: The Human Body Domainmentioning
confidence: 95%
“…Crucially, this approach allows them to show that differences in salience, both between and within taxonomical levels, correlate with naming preferences, including the fact that concepts that are more entrenched are more likely to be named with simplex forms. Later studies have shown that concepts with a higher degree of salience not only correlate with naming preferences, but also with decreased dialectal variation (Speelman and Geeraerts, 2008;Geeraerts and Speelman, 2010;Franco et al, 2019b). For example, in the semantic field of the human body, the Limburgish dialect dictionary only contains a single word for a highly salient concept like blood, whereas a lot more variation occurs for less salient concepts like the little dents between the knuckles, or bristly (w.r.t.…”
Section: Saliencementioning
confidence: 99%
See 1 more Smart Citation
“…In all cases, it was understood as a structure stored in our minds. Nevertheless, a simultaneous Western tendency was traced in regarding concepts as a reflection of language-unit meanings or simply as information activated by a word (Clausner & Croft, 1999;Croft & Cruse, 2004;Evans & Green, 2006;Franco et al, 2019. This was also supported by Eastern scholars (Nikitin, 2007;Zhabotinskaja, 2013).…”
Section: Introductionmentioning
confidence: 97%